Synergistic benefits of AMF: development of sustainable plant defense system - Boyno, Gökhan; Rezaee Danesh, Younes; Çevik, Rojbin; Teniz, Necmettin; Demir, Semra; Demirer Durak, Emre; Farda, Beatrice; Mignini, Amedeo; Djebaili, Rihab; Pellegrini, Marika; Porcel, Rosa; Mulet, José M. (Frontiers in Microbiology, 2025)
Arbuscular mycorrhizal fungi (AMF) are a ubiquitous group of soil microorganisms that form symbiotic relationships with the roots of over 80% of terrestrial plant species. These beneficial fungi are crucial in plant growth, nutrition enhancement, and abiotic and biotic stress resilience. This review explores the AMF synergistic benefits including their capacity to interact with plant roots system to enhance nutrient absorption, improve stress resilience, and confer disease resistance, and their potential applications in sustainable agriculture. The Review integrates recent insights illustrating the molecular processes responsible for improving plant defense mechanisms by AMF, including the modulation of signaling pathways. It highlights the importance of AMF-induced systemic resistance in enhanced abiotic and biotic stress resistance. Moreover, the article provides an integrative perspective on applying AMF toward sustainable plant protection. Within this context, we discussed how these fungi improve plant performance, including enhanced nutrient acquisition, increased tolerance to environmental stressors, and enhanced protection against pathogens by improving plant resistance to biotic stress through the activation of the plant immune system. We also examine the ecological significance of AMF in maintaining soil health and fertility and highlight the importance of incorporating their management into sustainable agricultural practices. Future research directions and innovative applications are also presented. The literature survey demonstrated these fungi's versatility in improving plant tolerance to several biotic and abiotic stresses. At the scientific level, these abilities are supported by several open-field experiments on different plant species. Available commercial formulations and positive ongoing research of AMF, in combination with other sustainable tools, highlight the solid research outline on these beneficial fungi.